Pemetaan Pola Sebaran Air Tanah Menggunakan Metode Geolistrik Untuk Membantu Masyarakat Mencari Aquifer Air Tanah di Desa Jada Bahrain Kecamatan Merawang - Janiar Pitulima; Guskarnali Guskarnali; Mardiah Mardiah (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
The service was carried out in Jada Bahrain Village, Merawang District using the wenner configuration geoelectric method based on the resistivity value (Ohm meter). This service is an initial service in analyzing the pattern of Res2DInv software results in the form of a resistivity cross section of the soil layer which is indicated to have groundwater.Measurements were carried out based on a survey design (trajectory) of 4 tracks with the length of each measurement track of 160 meters and a spacing between electrodes of 10 meters. The results of the service show that the soil layer on the measurement track obtained the groundwater distribution pattern in the service area has a relatively small resistivity. The soil layer in the form of sand containing groundwater is found at a depth above about 18.5 meters with a resistivity value ranging from 5.27-247 Ohm meters.